2018
DOI: 10.2147/ijn.s147969
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctional Sr- and Si-loaded titania nanotube coating of Ti surfaces by anodization-hydrothermal process

Abstract: Background Two frequent problems associated with titanium (Ti) surfaces of bone/dental implants are their corrosion and lack of native tissue integration. Methods Here, we present an anodization-hydrothermal method for coating Ti surfaces with a layer of silicon (Si)- and strontium (Sr)-loaded titania nanotubes (TNs). The Ti surfaces coated with such a layer (Si–Sr-TNs) were characterized with different techniques. Results The results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 27 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Lai et al reported that an osteogenic growth peptide coating on TiO 2 nanotubes increased the expression of collagen, Runx‐2, OPN, and OC and mineralization 29 . Moreover, many studies have reported that cell proliferation and differentiation are improved by the doping of Mg, Sr, and F ions on the nano surface 29‐31 . Ding et al studied the effect of nanotube diameters (30–80 nm) on the surface with the sandblasting with grit and acid etching (SLA) method.…”
Section: Introductionmentioning
confidence: 99%
“…Lai et al reported that an osteogenic growth peptide coating on TiO 2 nanotubes increased the expression of collagen, Runx‐2, OPN, and OC and mineralization 29 . Moreover, many studies have reported that cell proliferation and differentiation are improved by the doping of Mg, Sr, and F ions on the nano surface 29‐31 . Ding et al studied the effect of nanotube diameters (30–80 nm) on the surface with the sandblasting with grit and acid etching (SLA) method.…”
Section: Introductionmentioning
confidence: 99%
“…As orthopaedic implant success can be undermined by two leading causes, aseptic loosening and infection, implant coating are required to achieve inhibit microbial cells while still promoting the osteointegration. Many studies have focused on biofunctional NT to enhance their antibacterial activity or interactions with cells [20][21][22][23]. However, the biotribological and biocorrosion performances of NT, which play a key role in the long-term success of an implantation, are often missed.…”
Section: Introductionmentioning
confidence: 99%
“…Strontium has had its improved form to increase the proliferation of osteoblasts, promote the formation of new bone and osseointegration and also prevent bone dissolution. It is an indicated addition to improve the bioavailability and the bone induction of hydroxyapatite, and studies indicate that when replacing the calcium ion with strontium ion in hydroxyapatite, it alters the description of this but improves the mechanics of crystal growth 7 .…”
Section: ■ Introductionmentioning
confidence: 99%